Shalawat Kawakib Sya’ir in Maulid Diba’ by Shaykh Abdurrahman Ad-Diba’i: A Semiotic Analysis - Ngakidatul Hikmah (Institut Agama Islam Negeri Salatiga, 2022)
Shalawat Kawakib is the focus of this research because it is very familiar to the public and contains several signs that need to be explored semiotically. This research is conducted to investigate the signifier and signified in the sya'ir which then derives the meaning. This research employs Ferdinand de Saussure's semiotic approach to the Shalawat Kawakib sya'ir with a descriptive-qualitative method. The results demonstrate that Shalawat Kawakib's 16 stanzas have 23 signifiers, signs, and meanings such as: (1) نَبِيٌّ نُوْرُهُ يَجْلُو اْلغَيَاهِبْ as the signifier, while the sign is Rasul as the owner of light, the transmitter of the universe and erasing darkness. This sign means light from human beings who have the greatest influence on world civilization. (2) فَقَدْ حَصَلَ اْلهَنَا وَالضِّدُّ غَائِبْ as a signifier, the sign is that every soul that has met the Prophet feels happiness, while anxiety disappears. This sign implies that every soul that meets the Prophet feels happiness, while anxiety disappears. From the whole significance, a moral message is derived, such as emulating the morals of the Prophet Muhammad PBUH. by multiplying shalawat and commemorating every birthday. Life becomes peaceful if the heart is able to feel love for the Prophet, keeping the Messenger as the center of life, the guide for every step of goodness, and the light in the darkness.